Effects of Inhaled Corticosteroids on Bone in Asthma Patients - Saqib Ali (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Although inhaled corticosteroids are taken into the bloodstream, it is unclear how much damage they do to bones. The issue is crucial because 3% of people consistently use inhaled corticosteroids and could be doing for several decades. Method: In 195 adults (118 women) with asthmatic, aged 25 to 45, we examined the dose-response relationship between total inhaled corticosteroid dosage and bone mineralization concentration at the lumbar region and proximal femur. Participants had received only a little amount of systemic steroids and had routinely used an inhaled corticosteroid for a minimum of six months. Multiple regression analysis was employed to evaluate the total dosage of inhaled corticosteroid’s impact on the density of bones from surveys, computerized general practitioners’ data, and printed and handwritten general medical documents. Results: Treatment with inhaled corticosteroids lasted an average of 6 years (0–23), with a baseline total dose of 875 mg (87–4370). Both before and after adjusting for the influences of aging and gender, the results showed a negative correlation between the total dose of inhaled corticosteroid and skeletal mineral density at the lumbar region (L2-L4), femoral neck, and trochanter. An increase in inhaled corticosteroid dosage by twofold was linked to a 0•17 SD (95% CI 0•03-0•27) reduction in lumbar spine concentration of bone minerals... The femoral neck and trochanter all showed identical declines. The relationships remained strong after controlling for possible influencing variables such as regular exercise and previous use of oral, intranasal, cutaneous, and injectable corticosteroids. Conclusion: This investigation shows a link between the overall average dosage of inhaled corticosteroids and decreased bone mineralization concentration in asthmatic sufferers. Keywords: Corticosteroids, fracture, bone mineralization, inhaled, dosage, asthma, lumbar region, femur